2013
DOI: 10.1302/0301-620x.95b10.30541
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental knee replacement after high tibial osteotomy

Abstract: The outcome of high tibial osteotomy (HTO) deteriorates with time, and additional procedures may be required. The aim of this study was to compare the clinical and radiological outcomes between unicompartmental knee replacement (UKR) and total knee replacement (TKR) after HTO as well as after primary UKR. A total of 63 patients (63 knees) were studied retrospectively and divided into three groups: UKR after HTO (group A; n = 22), TKR after HTO (group B; n = 18) and primary UKR (group C; n = 22). The Oxford kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…Within recent years, there has been good evidence that arthroplasty after osteotomy is associated with excellent results despite being technically demanding. 38,40,52 Thus, by postponing primary arthroplasty even in severe osteoarthritis, osteotomies can improve the unsolved problem of impending multiple revision arthroplasties, especially in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Within recent years, there has been good evidence that arthroplasty after osteotomy is associated with excellent results despite being technically demanding. 38,40,52 Thus, by postponing primary arthroplasty even in severe osteoarthritis, osteotomies can improve the unsolved problem of impending multiple revision arthroplasties, especially in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if arthroplasty should be necessary within the further course because of persistent or reoccurring complaints from unicondylar osteoarthritis, a corrected axis and regained ligamentous stability might facilitate or enable the implantation of a UKA instead of a TKA in the first place in these cases, which would not have been possible in an ACL-insufficient knee with significant varus malalignment. 45,46 Functional improvements were reported by several authors after combined procedures of HTO and ACLR: A recently published review of 11 studies with simultaneous HTO and ACLR reported improvements in all subjective evaluations, regardless of the scoring system used. 28 A great heterogeneity regarding surgical technique, indication, and outcome measurement is present in the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…1-4 Accuracy of implant positioning and restoring the proper limb alignment are required for the long-term survival of the implants. 5 A neutral correction or slight undercorrection in the coronal alignment is advocated in the literature.…”
Section: Introductionmentioning
confidence: 99%